Fermentation of Agmatine in Streptococcus faecalis: Occurrence of Putrescine Transcarbamoylase - Roon, Robert J. (1972)
Putrescine transcarbamoylase, EC 2.1.3.x (carbamoylphosphate:putrescine transcarbamoylase), has been purified from Streptococcus faecalis 10C1 grown on agmatine as primary energy source. The formation of N-carbamoylputrescine from putrescine and carbamoylphosphate serves as a convenient and sensitive assay for this enzymatic activity. The enzyme catalyzes both the phosphorolysis arsenolysis of N-carbamoylputrescine. Arginine does not induce the synthesis of putrescine transcarbamoylase in S. faecalis. Furthermore, the putrescine transcarbamoylase activity is easily separated from ornithine transcarbamoylase activity by gel filtration on Sephadex G-100 indicating that the two activities are associated with different proteins. The significance of this new enzyme in the fermentation of agmatine and its relation to the other known transcarbamoylases are discussed.